SOME LIMNOLOGICAL FEATURES OF AL-HAMMAR MARSH SOUTH OF IRAQ AFTER RESTORATION - H. Talib, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Some Limnological features (electrical conductivity, pH, salinity, dissolved oxygen, water temperature, light penetration, turbidity, nutrients NO2, NO3, PO4) were used in current study to monitor Al-Hammar marsh (Al-Naggarah and Al-Burgah) south of Iraq monthly sampling for one year. The mean range of the following limnological parameters were recorded: water temperature ranged between 11.1 to 33 C˚, electrical conductivity ranged between 2453.3 to 6100 µs/cm, salinity ranged from 1.16 to 3.3 ‰, pH ranged between 7 – 8.6, water depth ranged between 0.7 to 1.9 m, light penetration ranged from 70 to 200 cm, dissolved oxygen ranged from 3.67 to 10.03 mg/l, NO2 ranged from 0.11 to 3.393 μg/l, NO3 ranged between 0.69 to 16.466 μg/l, PO4-3 ranged between 0.5 to 21.95 μg/l. According to the results, Al-Hammar marsh is rich in nutrients which can enhance their suitability for growing aquatic plants and phytoplankton. Seasonal variations and some fluctuations were observed in this marsh during different seasons for both sites. The results of this study initiate significant background information and database for physico-chemical variables of Al-Hammar Marsh.-